Editorial - Neves, Pedro Soares (BBDS - Black Book: Drawing and Sketching, 2025)
We invited contributions for 'Nature Drawing Nature', an online seminar co-organized by Pedro Soares Neves, Black Books: Drawing and Sketching Online Journal in collaboration with Sara Schneckloth and Kiera O’Toole. The seminar took place on April 3rd and 4th, 2025. Selected contributions explore the interconnectedness of humans and nature through the lens of drawing. As part of nature, everything we create—every line, every mark—emerges from and interacts with the environment. This theme emphasizes drawing as a tool for reflection, care, and awareness, urging us to consider the impact of our actions on the delicate balance of ecosystems. Inspired by ideas of biodiversity preservation as gestures of hope and responsibility, and considering drawing as an ecological act, we sought papers that addressed drawing as both a creative and ethical practice. This special issue comes partially from a collaboration with Shriya Malhotra.